Structural studies of the protein endostatin in fusion with BAX BH3 death domain, a hybrid that presents enhanced antitumoral activity - Chura-Chambi, Rosa Maria; Arcuri, Helen Andrade; Lino, Felipe; Versati, Natan; Palma, Mario Sergio [UNESP]; Favaro, Denize C.; Morganti, Ligia (Wiley, 2017)
Endostatin (ES) is an antiangiogenic protein that exhibits antitumor activity in animal models. However, the activity observed in animals was not observed in human clinical trials. ES-BAX is a fusion protein composed of two functional domains: ES, which presents specificity and is internalized by activated endothelial cells and the proapoptotic BH3 domain of the protein BAX, a peptide inductor of cellular death when internalized. We have previously shown (Chura-Chambi et al., Cell Death Dis, 5, e1371, 2014) that ES-BAX presents improved antitumor activity in relation to wild-type ES. Secondary and tertiary structures of ES-BAX are similar to ES, as indicated by homology-modeling studies and molecular dynamics simulations. Tryptophan intrinsic fluorescence and circular dichroism spectroscopy corroborate these data. 15N HSQC NMR indicates that ES-BAX is structured, but some ES residues have suffered chemical shift perturbations, suggesting that the BH3 peptide interacts with some parts of the ES protein. ES and ES-BAX present similar stability to thermal denaturation. The production of stable hybrid proteins can be a new approach to the development of therapeutic agents presenting specificity for tumoral endothelium and improved antitumor effect.
Keywords: angiogenesis; apoptosis; BAX; BH3 domain; circular dichroism; endostatin; molecular modeling